2015
DOI: 10.5194/isprsarchives-xl-1-w4-299-2015
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Area Index Estimation in Vineyards From Uav Hyperspectral Data, 2d Image Mosaics and 3d Canopy Surface Models

Abstract: Commission I,WG ICWG I/Vb KEY WORDS: Precision agriculture, biomass, crop, narrow band indices ABSTRACT:The indirect estimation of leaf area index (LAI) in large spatial scales is crucial for several environmental and agricultural applications. To this end, in this paper, we compare and evaluate LAI estimation in vineyards from different UAV imaging datasets. In particular, canopy levels were estimated from i.e., (i) hyperspectral data, (ii) 2D RGB orthophotomosaics and (iii) 3D crop surface models. The comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 10 publications
1
45
0
1
Order By: Relevance
“…Mathews and Jensen (2013) compared LAI estimated by a digital camera aboard an unmanned aerial vehicle to indirect, ground-based estimates of LAI using a ceptometer for vineyards, and reported r 2 = 0.57. Kalisperakis et al (2015) also estimated LAI of vineyards using an unmanned aerial vehicle, but they used both digital photography and hyperspectral sensors, and compared LAI estimated by remote sensing to Table 7. Discrepancies between measured and calculated LAI for each allometric model tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathews and Jensen (2013) compared LAI estimated by a digital camera aboard an unmanned aerial vehicle to indirect, ground-based estimates of LAI using a ceptometer for vineyards, and reported r 2 = 0.57. Kalisperakis et al (2015) also estimated LAI of vineyards using an unmanned aerial vehicle, but they used both digital photography and hyperspectral sensors, and compared LAI estimated by remote sensing to Table 7. Discrepancies between measured and calculated LAI for each allometric model tested.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, studies using unmanned aerial vehicles, high spatial resolution satellites, active lasers, and novel algorithms have demonstrated that remote sensing can provide meaningful LAI estimates (provided these can be tied to minimal groundtruth estimates). Some examples include row crops (Marshall and Thenkabail, 2015;Kross et al, 2015), vineyards (Mathews and Jensen, 2013;Kalisperakis et al, 2015), spruce forests (Solberg et al, 2009), and rugged terrain dominated by mixed pine forests (Morsdorf et al, 2006).…”
mentioning
confidence: 99%
“…[15] estimated the leaf area index (LAI) of a vineyard with a conventional digital camera (Canon PowerShot) mounted on a micro-UAV using the structure from motion (SfM) technique. In the same way, [16] estimated LAI of a vineyard using data from a hyperspectral camera (VNIR imaging sensor) and a low-cost standard RGB camera (GoPro Hero3) onboard a UAV system. In this study, the determination coefficient (r 2 ) for the relationship between ground truth LAI and 2D GRVI map from the aerial RGB ortho-mosaic was 0.73.…”
Section: Perspectives and General Study Limitationsmentioning
confidence: 99%
“…Furthermore, the vineyards can be frequently surveyed to study ongoing phenomena at different phenological stages. Recent studies have demonstrated that high-resolution RGB images obtained by low-cost cameras can be used to monitor spatial variability of vine biophysical parameters [15,16]. Nevertheless, for an accurate evaluation of vineyard attributes from very high-resolution RGB imagery, automated procedures are required to rapidly extract the information coming from the vegetation (vine canopy pixels).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal imager and hyperspectral sensor in visible-NIR bands have been used on fixed wing and quadcopter platforms (Buettner and Roeser, 2013;Chrétien et al, 2015). UAS hyperspectral imagery has been used for leaf area index estimation (Kalisperakis et al, 2015;Proctor and He, 2015), while UAS thermal images have been used to monitor stream temperatures (Jensen et al, 2012) and roof heat losses (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%